Unfair “Fair Value” in Illiquid Markets: Information Spillover Effects in Times of Crisis - Dontoh, Alex; Elayan, Fayez A.; Ronen, Joshua; Ronen, Tavy (Management Science, 2021)
We investigate the effects of write-downs on market prices and volumes under fair value accounting. We also examine the prominent role that illiquidity plays in exacerbating the direct and spillover effects of exit valuation on equity and credit default swap (CDS) markets. Using hand-collected data on write-down announcements made during and after the 2007–2009 financial crisis, we find that firms that wrote down assets in accordance with fair value rules experience significant abnormal negative stock returns and spikes in the CDS premiums written on their obligations; similar firms without write-downs exhibit sympathetic and significant negative abnormal returns and positive premiums. We find that both the direct effect of the write-downs and the indirect spillover effects resulting from crisis-related illiquidity in the markets for financial assets (affecting the magnitude of write-downs) and in the securities markets (affecting the reaction to the write-downs) during the financial crisis go beyond normal direct and information transfer effects and may have contributed to the adverse consequences of the crisis. This paper was accepted by Shiva Rajgopal, accounting.